ANALYSIS OF THE PERFORMANCE OF TRANSIT AREA OF SIDOARJO STATION AS A TRANSIT ORIENTED DEVELOPMENT (TOD) AREA - Muhammad Hidayat Isa; Adjie Pamungkas; Rimadewi Suprihardjo (Journal of Architecture&ENVIRONMENT, 2014)
The solving of traffic congestion has led to innovative strategies that promote the integration of transport system, one of which is through the concept of Transit Oriented Development (TOD). The movement of the population with high use of private vehicles in Surabaya-Sidoarjo corridor has caused congestion problems. However, the efforts done are still focused on the improvement of the capacity of the road network. This effort is partial and temporal, which means that in the long term it will continue to cause problems. For the development of mass transit in the north-south corridor, specifically on the side of Surabaya, the transit area is already in the planning stages and brings the concept of TOD. Therefore, it is necessary to study and examine TOD in Sidoarjo side, especially in the transit area of Sidoarjo station, which has the highest passenger movement in the Surabaya-Sidoarjo corridor.This study aims to analyze the performance of transit area of Sidoarjo Station as a TOD area. The analytical method used is descriptive statistical analysis and walkthrough analysis. Descriptive statistical analysis used includes the analysis of measures of central tendency, percentages and ratios, and graphs. Meanwhile, the walkthrough analysis used is the linear side view. Based on the analysis, the performance of transit area of Sidoarjo Station as TOD area is relatively low at 23.5%. Only four of the seventeen variables meet the performance standards. Those four variables are BCR (Building Coverage Ratio), percentage of road way area, pedestrian way connectivity, and percentage of parking lot.